Shakespeare som indre supervisor - Møhl, Bo (Psyke & Logos, 2022)
Murray Cox og Alice Theilgaard: Shakespeares as Prompter. The amending imagination and the therapeutic process (foreword by Adrian Noble and Ismond Rosen). Jessica Kingsley Publishers. 480 p. Pris: 22,50£